2016
DOI: 10.1186/s12879-016-1546-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of changing from staining to culture techniques on detection rates of Campylobacter spp. in routine stool samples in Chile

Abstract: BackgroundCampylobacter is a leading cause of bacterial gastroenteritis, but sensitive diagnostic methods such as culture are expensive and often not available in resource limited settings. Therefore, direct staining techniques have been developed as a practical and economical alternative. We analyzed the impact of replacing Campylobacter staining with culture for routine stool examinations in a private hospital in Chile.MethodsFrom January to April 2014, a total of 750 consecutive stool samples were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
(35 reference statements)
0
13
0
2
Order By: Relevance
“…A pesar del escaso diagnóstico microbiológico en el medio nacional, en el período 2015-2016 se notificaron tres brotes de enfermedades trasmitidas por alimentos (ETA) atribuibles a Campylobacter spp. 14 .…”
Section: Diagnóstico Microbiológico Y Prevalencia De Campylobacter Sppunclassified
See 1 more Smart Citation
“…A pesar del escaso diagnóstico microbiológico en el medio nacional, en el período 2015-2016 se notificaron tres brotes de enfermedades trasmitidas por alimentos (ETA) atribuibles a Campylobacter spp. 14 .…”
Section: Diagnóstico Microbiológico Y Prevalencia De Campylobacter Sppunclassified
“…De hecho, en el caso de alimentos, este patógeno no se encuentra incluido en el Reglamento Sanitario de los Alimentos (RSA) del Ministerio de Salud de Chile 21 y los datos de la presencia de especies de Campylobacter spp. en plantas de procesamiento chilenas son limitados 14 . Sin embargo, algunos estudios desarrollados en el centro y sur de Chile han demostrado que C. jejuni y C. coli presentan una alta prevalencia en muestras fecales de animales de granja y en la carne derivada de éstos 22,23 .…”
Section: Diagnóstico Microbiológico Y Prevalencia De Campylobacter Sppunclassified
“…Nevertheless, recent reports suggest that the burden of campylobacteriosis in Chile has been greatly underestimated due to suboptimal diagnostic protocols in both public and private health centers [15]. A recent study showed a 10-fold increase of the detection rate of Campylobacter in human stool samples after changing from microscopic stool examination by Gram staining (the routine protocol in Chilean health centers) to culturedependent techniques [16]. In another study from the same group, Campylobacter spp.…”
Section: Introductionmentioning
confidence: 99%
“…The available clinical, laboratory and epidemiological data have been produced mainly in developed countries, where national surveillance programs for campylobacteriosis exist 8 . In general, developing countries do not have this kind of programs or they are just implementing them, which does not allow reliable and conclusive epidemiological data 9 . On the other hand, in developing countries, Campylobacter is not routinely diagnosed as enteric pathogens, thus, their frequency in infant community-acquired diarrhea is commonly underestimated 10 .…”
mentioning
confidence: 99%